The Effect of Food Quality and Brand Equity on Tourist Experience Mediated by Satisfaction at Local Restaurants in Banda Aceh City (International Journal of Scientific Research and Management (IJSRM), 2025)
This study aims to analyze the effects of food quality and brand equity on tourist experience, with satisfaction as a mediating factor, at local restaurants in Banda Aceh City. The population for this study comprises all consumers of local restaurants in Banda Aceh City. A non-probability sampling technique was employed, specifically purposive sampling, which involves selecting samples based on specific criteria such as tourists’ experiences at local restaurants. The sample size was determined to be 10 times the number of research indicators. Since this study used 20 indicators, the minimum required sample size was 200 respondents (10 × 20 = 200). Partial Least Squares (PLS) was used as the analysis method. The results indicate that food quality has a positive effect on satisfaction; brand equity has a positive effect on satisfaction; food quality positively influences tourist experience; brand equity positively influences tourist experience; and satisfaction positively affects tourist experience. Furthermore, mediation analysis revealed that satisfaction partially mediates the effects of food quality and brand equity on tourist experience at local restaurants in Banda Aceh City.